Analisis Situasional Bank Sampah Sebagai Metode Pengelolaan Sampah - Irhamna Mandili; Amron Zarkasih; Rika Syahmewah Munthe; Erni Wahyuni (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
Waste is a big problem in society and requires special handling. A new paradigm in waste management is needed to overcome this problem. Waste bank is the right solution in overcoming the waste problem in society. The purpose of this article is to obtain the results of a situational analysis of waste banks as a method of waste management. The results of the analysis are expected to be a reference in the implementation of the waste bank program. The analysis is carried out by reviewing the results of research and community service separately. References are obtained from online libraries. The results of the review are used as material for analysis of the waste bank program. The results of the analysis are used as the basis for compiling recommendations for the implementation of related community service activities. The results of the analysis provide 5 recommendations for community service activities. Recommendations include socialization, communication, optimization assistance, and local government coordination.